Brain Characteristics in Patients With Myelin Oligodendrocyte Glycoprotein Antibody‐Associated Disorder by 7.0 Tesla MRI - Lei Su; Joseph Kuchling; Chenyang Gao; Thoralf Niendorf; Carsten Finke; Zhe Zhang; Ai Guo; Jing Jing; De‐Cai Tian; Yu‐Jing Li; Mengting Zhang; Xiaoyu Shi; et al. (Annals of Clinical and Translational Neurology, 2025)
ABSTRACT Background Myelin oligodendrocyte glycoprotein antibody‐associated disease (MOGAD) can radiographically mimic multiple sclerosis (MS) and neuromyelitis optica spectrum disorder (NMOSD). The disease hallmarks cortical lesion, central vein sign (CVS) and paramagnetic rim lesions identified in MS have not yet been comprehensively investigated in MOGAD. Methods We have characterized 45 patients with MOGAD using 7.0 Tesla (7 T) MRI at two academic research hospitals in China and Germany. 7 T MRI, laboratory, and clinical data were collected. The classification of cortical lesions, proportion of CVS, and the phase shifts of lesions on susceptibility weighted imaging were analyzed. Results Of the 45 patients enrolled with MOGAD, 282 lesions were identified. We further detected 31 (11%) cortical lesions including leukocortical, intracortical, and subpial types, of which intracortical lesions (16/31, 52%) were frequently involved. CVS was identified in 53 (19%) lesions of 21 (47%) patients, 154 (55%) lesions showed multiple veins sign (MVS) in 30 (67%) patients. The number (4.3 ± 6.0 vs. 1.5 ± 2.1, p = 0.0049) and percentage (52% vs. 18%, p < 0.0001) of MVS lesions for each MOGAD patient were higher than those of CVS. Eight patients (18%) had 39 (14%) lesions of hypointense signal with paramagnetic phase shifts on SWI, showing nodular phase changes and irregular borders in appearance. Conclusions In our observational MOGAD cohort, all three types of cortical lesions were recognized, with intracortical lesions being the most common. The number and proportion of lesions with MVS were higher than those with CVS. Lesions with paramagnetic phase changes were rare and non‐rim‐like in appearance. These findings provide a better understanding of the underlying pathology of MOGAD and will help in the differentiation of MOGAD from other demyelinating disorders.